Dampak Diskriminasi Ras Terhadap Tokoh Utama Dalam Cerpen Rihlah Ghurbah Karya ‘Awad Al-Nawasreh; Analisis Sosiologi Sastra - Syarifuddin Syarifuddin; Rahmah Zakiyah (Fakultas Adab dan Humaniora UIN Raden Fatah, 2022)
This study aims to describe the impact of racial discrimination on the main character in the short story